A bibliometric and network analysis of the field of computational linguistics. (30th January 2015) - Radev, Dragomir R.; Joseph, Mark Thomas; Gibson, Bryan; Muthukrishnan, Pradeep
Abstract : The ACL Anthology is a large collection of research papers in computational linguistics. Citation data were obtained using text extraction from a collection of PDF files with significant manual postprocessing performed to clean up the results. Manual annotation of the references was then performed to complete the citation network. We analyzed the networks of paper citations, author citations, and author collaborations in an attempt to identify the most central papers and authors. The analysis includes general network statistics, PageRank, metrics across publication years and venues, the impact factor and h‐index, as well as other measures.